Improving student teachers' TPACK self-efficacy through lesson planning practice in the virtual platform - Kapici, Hasan Ozgur; Akcay, Hakan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
How teachers use technology efficiently in their classes is an important issue because learning environments are also affected by rapid developments in instructional technology. In the current study, we investigated how designing an inquiry-based technology-enhanced lesson plan on the virtual platform influences the TPACK (Technological Pedagogical Content Knowledge) self-efficacy of pre-service teachers and also how they integrated educational technology into their lesson plans. A total of 38 undergraduate students at a teacher education programme participated in the study. Data were gathered by the self-efficacy scale and the lesson plans developed by the pre-service teachers. The findings revealed a significant increase in the TPACK self-efficacy of the pre-service teachers after they designed an inquiry-based technology-enhanced lesson plan on the virtual platform. Besides, lesson plan analysis showed that pre-service teachers generally followed the phases of inquiry-based learning and integrated online scaffolding tools and virtual laboratories into their plans at a moderate level.
Keywords: TPACK; technology integration; self-efficacy; lesson plan; pre-service teacher; PEDAGOGICAL CONTENT KNOWLEDGE; PRESERVICE ELEMENTARY TEACHERS; SCIENCE TEACHERS; MIXED METHODS; BELIEFS; SUPPORT; EDUCATION; DESIGN; MATHEMATICS; Education & Educational Research